2017
DOI: 10.1557/jmr.2017.298
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous SiO2/C composite as anode material for lithium-ion batteries

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…A main strategy to overcome the challenges of silica as an anode material has been to use carbon as a conductive matrix material. Carbon coating provides an effective solution to the above issue, improving the cycling stability by buffering the volume expansion of the silica particles [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, it is desirable to design a sustainable and eco-friendly preparation route for C/SiO 2 composites.…”
Section: Introductionmentioning
confidence: 99%
“…A main strategy to overcome the challenges of silica as an anode material has been to use carbon as a conductive matrix material. Carbon coating provides an effective solution to the above issue, improving the cycling stability by buffering the volume expansion of the silica particles [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Therefore, it is desirable to design a sustainable and eco-friendly preparation route for C/SiO 2 composites.…”
Section: Introductionmentioning
confidence: 99%
“…New applications of HSPs as electrolyte stabilizers or anodes in lithium ion batteries have been reported [17,[99][100][101][102]. In one such example, Zhang et al used HSP-based films filled with liquid electrolytes as solid electrolytes that show lithium-ion conductivities in the order of approximately 1 mS, while being mechanically stable and mitigating the penetration of dendrites [99].…”
Section: Energy Storagementioning
confidence: 99%
“…Cao et al demonstrated that HSPs embedded in porous carbon are promising anodes for lithium ion batteries. Such electrodes can provide a specific capacity of 910 mA h g −1 at a rate of 200 mA g −1 after 150 cycles, while exhibiting reasonable rate capability [100]. HSPs made of carbon-coated silica nanoparticles and several other combinations of carbon and HSPs have also been demonstrated as battery anodes (as shown in Figure 5) [99][100][101][102].…”
Section: Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Lithium-ion batteries (LIBs) have been widely used in portable devices, vehicle mounted equipment, and electrochemical energy storage owning to their environmental friendliness, high energy density, and long lifespan [1][2][3][4][5]. As the commercial anode material in LIBs, graphite has a low theoretical capacity of 372 mAh g −1 , which is difficult to meet the ever-growing demands of high-energy-density [6][7][8]. Therefore, momentous efforts have been made to exploring an ideal alternative anode with high lithium storage capacity.…”
Section: Introductionmentioning
confidence: 99%